Global Centroid Distribution of Magnetized Layer From World Digital Magnetic Anomaly Map. Issue 12 (22nd December 2017) - Tanaka, Akiko
Abstract : Global distribution of the centroid of magnetic layer, Z o, was estimated from spectral analysis of aeromagnetic and marine magnetic anomalies using recently released new global digital magnetic anomaly data, World Digital Magnetic Anomaly Map (WDMAM) version 2.0. Z o distribution provides a comprehensive view of regional‐scale trends of lithospheric thickness; Z o is generally shallower in oceanic ridges and deeper older continents, which is consistent with previous works. Z o is closely related to reasonable average thermal regime, and its correspondence with tectonic regime indicates that Z o is useful to delineate regional crustal thermal structure. It is expected that Z o combined with multidisciplinary data should help to infer geophysical and geological information in less explored regions. Key Points: Global distribution of the centroid of magnetic layer, Z o, is revealed Z o can be used as a proxy for the thermal structure